Wavefront reconstruction from non-modulated pyramid wavefront sensor data using a singular value type expansion. (22nd January 2018) - Hutterer, Victoria; Ramlau, Ronny
Abstract: The new generation of extremely large telescopes includes adaptive optics systems to correct for atmospheric blurring. In this paper, we present a new method of wavefront reconstruction from non-modulated pyramid wavefront sensor data. The approach is based on a simplified sensor model represented as the finite Hilbert transform of the incoming phase. Due to the non-compactness of the finite Hilbert transform operator the classical theory for singular systems is not applicable. Nevertheless, we can express the Moore–Penrose inverse as a singular value type expansion with weighted Chebychev polynomials.